THE EFFECT OF E-TRUST AND ONLINE CUSTOMER REVIEW ON PURCHASE DECISIONS FOR SOMETHINC SKINCARE PRODUCTS ON THE SHOPEE PLATFORM - Irma Rasifa; Ahmad Johan; Muhamad Hidayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The growth of e-commerce has changed how Indonesian consumers evaluate and purchase skincare products, particularly because online buyers cannot test products directly before purchase. This study examines the influence of e-trust and online customer review on purchase decisions for Somethinc skincare products on Shopee. The research used a quantitative design with descriptive and verification approaches. The population consisted of consumers who had purchased Somethinc skincare through Shopee, and 100 respondents were selected using non-probability purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination with IBM SPSS Statistics 27. The findings indicate that e-trust, online customer review, and purchase decision are all in the high category. Partially, e-trust has a positive and significant effect on purchase decision (t = 3.335; sig. = 0.001), while online customer review has a stronger positive and significant effect (t = 6.100; sig. < 0.001). Simultaneously, both variables significantly affect purchase decision (F = 105.232; sig. < 0.001). The adjusted R square of 0.678 shows that e-trust and online customer review explain 67.8% of purchase decisions